The Role of the Water Police Unit in Addressing the Use of Environmentally Unfriendly Fishing Gear in the Waters of Cirebon City - Syahputra, Deny Halim (Advances in Police Science Research Journal, 2024)
The background of this research is the high number of use of fishing gear that is not environmentally friendly by fishermen who live in the Cirebon City Police area. The focus of this research is the role of the Cirebon City Water Police Unit in preventing the use of fishing gear that is not environmentally friendly to fishermen. The most effective effort is prevention or prevention. Therefore a study was conducted aimed at finding out what had been done by the Cirebon City Water Police Unit, knowing what factors influenced the activity and how to optimize the activity. This research was conducted with qualitative methods, using descriptive methods and data collection techniques in the form of interviews, observations, and document review. The results of the study found that community development efforts analyzed using the concept of bhabinkamtibmas were appropriate because these activities aimed to maintain public safety and order. Less than optimal based on management theory due to several factors, namely the very small number of personnel of the Cirebon City Water Police Unit, the budget factor and the inadequate facilities and infrastructure. Based on the results of the study, the authors suggest adding personnel to the Cirebon City Water Police Unit so that they can carry out counseling activities more optimally. The author also suggests adding facilities and infrastructure such as patrol boats that will be used for preventive efforts. Because with more adequate infrastructure, it will be more optimal the results of fishermen’s coaching to realize Kamtibmas